Insurance And Insurance Purchase Decision - Rabihah Md Sum; Norhafiza Nordin (Malaysian Financial Planning Council, 2024)
Insurance is a business of uncertainty. On the one hand, insurance works in the presence of uncertainty. On the other hand, insurance is supplied by organisations seeking to make profits out of the uncertainty. The business of an insurer is to manage the collective risks passed to it by its policyholders. Insurance is not the only tool to cope with risk or uncertainty. There are other tools to cope with risk and uncertainty, which fall under the area of risk management. However, insurance is useful for risks with negative consequences i.e. risks defined as the danger of incurring losses such as loss of an asset, loss of limbs and loss of life